Regulatory domains of the Gmhsp17.5-E heat shock promoter of soybean. - Czarnecka, E (1989)
Promoter domains required for in vivo transcriptional expression of soybean heat shock gene Gmhsp17.5-E were identified by insertion-deletion mutagenesis with transgenic expression monitored in Agrobacterium tumefaciens-incited tumors of sunflower. Removal of the TATA-distal domain from position -1175 to position -259 had little effect on overall activity. The four regions contributing to promoter activity identified by this study all map within 244 base pairs from the start of transcription. The most distal cis-acting element of major significance was located from -244 to -179 and contains a conserved TATA-dyad motif centered at -220. Sequences from -179 to -40 comprise the TATA-proximal domain and include an AT-rich region and two sites containing heat shock consensus elements (HSEs). Deletion of the HSE centered at -93 (site 2) severely reduced transcriptional activity. Heat-inducible expression was also eliminated by internal deletion of either the TATA motif or the overlapping HSEs at site 1, indicating that each of these regions is also a major determinant of promoter activity.